Evaluation of eating disorders, kinesophobia and disfunctional attitudes in patients with type 2 diabetes mellitus - Aykut Turhan; Bülent Albayrak; Ayşe Çarlıoğlu; Nermin Gündüz; Havva Tuğba Kiper Yılmaz; Nazlıgül Karaüzüm Yalçın (National Scientific Medical Center, 2022)
Aim: Eating disorders (EDs), dysfunctional attitudes (DAs), and limitation of movement due to kinesiophobia, which are more common in patients with type 2 diabetes mellitus (T2DM), may contribute to poor metabolic control, weight gain, disregard for treatment, and an increased prevalence of microvascular and macrovascular complications; however, current evidence is limited to small studies and restricted measures. In this study, these characteristics were assessed in patients with T2DM relative to controls, and factors independently associated with ED, DA and kinesiophobia were examined. Material and methods: This case-control study was conducted between July 2018 and December 2018 at the Departments of Endocrinology and Psychiatry of Erzurum Regional Training and Research Hospital, Erzurum, Turkey. A total of 150 patients diagnosed with T2DM and 150 healthy controls were included. The Eating Attitudes Test (EAT), Dysfunctional Attitude Scale (DAS), and Tampa Scale for Kinesiophobia (TSK) were applied. Results: Median age in the control group was 38 (IQR: 27 - 47) years, and 56 (IQR: 46 - 61) years in the patient group. Women comprised 67.3% of controls and 61.3% of patients. Although all scale scores were higher in the patient group compared to controls, the possible relationships were not confirmed by multiple linear regression analysis. Significant factors independently associated with higher DAS score were high age (p=0.043), high body mass index (p=0.021) and presence of comorbidity (p=0.019). Significant factors associated with higher TSK score were high age (p<0.001) and high BMI (p=0.001). High age (p<0.001) was the only parameter associated with higher EAT score. The presence of T2DM was not found to be an independent factor associated with any of the scores. Conclusion: Our results show that, rather than the presence of T2DM, other patient characteristics were likely to be more influential on ED, DA and kinesiophobia. These show that older patients with T2DM who have comorbidities or DM-related complications are more likely to benefit from management that account for these characteristics.